ANALISIS KELAYAKAN USAHA RANGKAIAN BUNGA PADA BROMELIA FLORIST - Viona Olivia Idony (2020)
Cut flowers are used to express the feelings of sympathy of the heart to those who love the excitement or the joy of a success. This time, I show the market of the mother market of the ipotong has expanded. The expansion of ipasar ipangsa will give iprospek both the farmers and the traders of cut fruit. The purpose of this study is to examine the business feasibility of Bromelia Florist. The analytical method used is the analysis of non-financial aspects and financial assumptions. Based on the results of research conducted, non-financial aspects are feasible except management aspects that are needed improvement in these aspects. While the financial aspect was stated to be feasible because the NPV was Rp 681,204,833, IRR 153, Net B / C was 11,423, the payback period was 2 months and the PI was 1.15. Based on the results of sensitivity analyzes using Microsoft Exel and Lindo Software. The results of the sensitivity analysis on Microsoft Exel use the switching value method while the Lindo Software uses a linear programming method by finding the optimum production capacity.